2015
DOI: 10.1002/prep.201400151
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature and Strain Rate on the Dynamic Fracture Properties of HTPB Propellant

Abstract: [a] 1IntroductionHydroxyl-terminated polybutadiene (HTPB) propellant is widely used for the propulsion of missile and space launch vehicles. The solid propellant grain mays ubject to loads such as vibration, impact, among others, during shipping, ignition pressurization, and storage, which may cause damage as microcrack and cavity.Acrack propagating in ap ropellant grain creates extra surface area for burning which affectst he ballistic performance of the rocket motor. Especially under the ignitionp ressuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…And its mechanical properties depend on the properties of the matrix, concentration of the components, particle size, particle distribution, and the quality of the interface between polymeric binder and filler. Over the past few decades, a great amount of work has been done to study mechanical properties of the solid propellant under different loading forms and experimental conditions [5–10], like tension/compression, low/middle/high strain rate, and environment temperature. However, these studies can't truly reflect the mechanical properties of solid propellants at the ignition condition, which work under the confining pressure condition.…”
Section: Introductionmentioning
confidence: 99%
“…And its mechanical properties depend on the properties of the matrix, concentration of the components, particle size, particle distribution, and the quality of the interface between polymeric binder and filler. Over the past few decades, a great amount of work has been done to study mechanical properties of the solid propellant under different loading forms and experimental conditions [5–10], like tension/compression, low/middle/high strain rate, and environment temperature. However, these studies can't truly reflect the mechanical properties of solid propellants at the ignition condition, which work under the confining pressure condition.…”
Section: Introductionmentioning
confidence: 99%
“…Liu [4] developed a probabilistic crack growth model to predict crack growth behavior, and found that the local damage characteristics near the crack tip had strong effects on crack growth behavior [5]. Long et al [6] investigated the influence of temperature and strain-rate on HTPB propellant dynamic fracture properties. When the temperature decreases and the strain-rate increases, the dynamic initial fracture toughness increases.…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed that the microdefects (debonding, microholes, microcracks, etc.) in the material gradually formed and increased with the increase of deformation under the action of external load [7,8]. Therefore, it must be considered of the effects of loading history, temperature and strain rate on the mechanical properties of materials under finite deformation.…”
Section: Introductionmentioning
confidence: 99%